UNDP Digital Leadership Learning Modules - UNDP (United Nations Development Programme, 2022)
In order to support the digital transformation of government operation s Digital Learning Modules for Civil Servants are available, an off-th e-shelf package of capacity development in form of replicable training modules to empower public servants at both the local and central gove rnment level to be leaders of digital transformation for delivering be tter public services. The modules cover a multitude of fundamental are as: comprehending digital government and services, human-centered desi gn for inclusivity and agile learning cycles; feature the importance o f security and privacy, the value of data and how to manage data and t echnology related risks; spotlight the key role of supportive leadersh ip and offer practical tools for assessing and overcoming main barrier s to ensure a successful digital transformation journey.